PENGARUH BIAYA PENDIDIKAN, LOKASI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN SISWA PADA SMK PAB 2 HELVETIA - Amalia Br Pakpahan; Wisnu Rayhan Adhitya (FEB Universitas Maritim Semarang, 2023)
Education plays an important role in all aspects of human life. Education is the most effective tool to improve the quality of individuals to be more productive. Competition between formal educational institutions, especially at the Vocational High School (SMK) level, so that schools compete to improve the quality and quality of education to attract attention and seize market share and offer the services provided. Therefore, schools must design strong marketing strategies in order to make students interested and satisfied with the services provided. Several aspects that affect student satisfaction such as education costs, location and quality of service. This study aims to determine and analyze which factors are the most dominant influencing student satisfaction among education costs, location and service quality. The population in this study were 855 students at SMK PAB 2 Helvetia. With the Slovin formula, the number of samples obtained is 86 students of SMK PAB 2 Helvetia. Data were taken by distributing questionnaires to students which were then measured using a Likert scale. The data analysis technique used Multiple Linear Regression. This study uses SPSS 20 as data processing. The results showed that simultaneously the cost of education, location and service quality had a significant positive effect on student satisfaction. While partially the cost of education, location and service quality have a significant positive effect on student satisfaction.